Adaptasi Alat Ukur The Employee Engagement Scale (EES) - Karima Astari; Anissa Lestari Kadiyono; Megawati Batubara (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This study aims to adapt the measuring instrument, The Employee Engagement Scale (EES), to the employee population in Indonesia by involving a total sample of 213 employees. The Employee Engagement Scale (EES) developed by Shuck et al. (2016) is an instrument consisting of three dimensions, namely Cognitive Engagement, Emotional Engagement, and Behavioral Engagement, with 12 items to measure employee engagement. The adaptation process follows the ITC Guidelines for Translating and Adapting Test (Second Edition). Reliability analysis was conducted by looking for Cronbach's alpha coefficient, and validation was carried out using confirmatory factor analysis (CFA). The results showed that the Indonesian version of the Employee Engagement Scale (EES) had good Cronbach's Alpha reliability (.914). The validity of the Confirmatory Factor Analysis (CFA) analysis showed that the model fit (p=.201), with other parameters to test the model's accuracy, including RMSE, GFI, CFI, TLI, and NFI, show that all of them meet the fit criteria. Thus, the results of this study indicate that the 12 items contained in the adapted Employee Engagement Scale (EES) can be used to measure employee engagement in Indonesia.